Sensory Connotations of the formula (Afeal) in the holy Quran (Raparin Journal of Humanities (RJH), 2019)
This study aims at investigating the Quranic words which are formed using the metrical unit "Formula afeal function on Sensual meanings”. It is well-known that understanding semantics in Quran is based upon understanding the connotation of its lexical items in addition to the structures used in it. The current study also enriches the Quranic and linguistic studies. The significance of this study lies in the fact that it locates the words which are formed using the metrical unit "Formula 'afeal" then reveals the semantic and morphological meanings of this group of words. It also sheds light on some linguistic phenomena that are usually related to such kind of studies. The study throws light on the role of context in determining the semantic meaning, regarding attentively both synonymy and polysemy and referring to some examples of collocation.